2008
DOI: 10.1037/0096-1523.34.2.427
|View full text |Cite
|
Sign up to set email alerts
|

The mental representation of music notation: Notational audiation.

Abstract: This study investigated the mental representation of music notation. Notational audiation is the ability to internally "hear" the music one is reading before physically hearing it performed on an instrument. In earlier studies, the authors claimed that this process engages music imagery contingent on subvocal silent singing. This study refines the previously developed embedded melody task and further explores the phonatory nature of notational audiation with throat-audio and larynx-electromyography measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 47 publications
6
99
2
4
Order By: Relevance
“…Previous authors have noted that ability to perform notation audiation varies widely in musicians (Brodsky et al, 2003(Brodsky et al, , 2008. Evidence from the present experiment supports this suggestion.…”
Section: Discussion O F F I N D I N G Ssupporting
confidence: 92%
“…Previous authors have noted that ability to perform notation audiation varies widely in musicians (Brodsky et al, 2003(Brodsky et al, , 2008. Evidence from the present experiment supports this suggestion.…”
Section: Discussion O F F I N D I N G Ssupporting
confidence: 92%
“…For example, Mackay (1981) demonstrated that sentence production improves not only when producing these out loud but also silently. Beneficial effects of imagery have also been observed in typing (Wohldmann et al, 2007), music (Brodsky et al, 2008), dance (Golomer et al, 2008) and surgery (Hall, 2002). Analogous mechanisms may be involved when learning from observation, i.e.…”
Section: Introductionmentioning
confidence: 87%
“…Musicians may engage motor and auditory processes when reading musical notation (Brodsky, Kessler, Rubinstein, Ginsborg, & Henik, 2008), as they did in the auditory imagery task reported here. Despite this possibility, a distinction between the motor and auditory imagery tasks is supported by the fact that scores on the two measures did not correlate with one another, and they correlated differentially with recognition following the different learning conditions.…”
Section: Discussionmentioning
confidence: 99%